Reservation Wages and Labor Supply - Iris Kesternich; Heiner Schumacher; Bettina Siflinger; Franziska Valder (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Survey measures of the reservation wage reflect both the consumption-leisure trade-off and job search concerns (the arrival rate of job offers and the wage distribution). We examine what a survey measure of the reservation wage reveals about labor supply when search concerns are absent. To this end, we combine the reservation wage measure from a large labor market survey with the reservation wage for a one-hour job that we elicit in an online experiment. The two measures show a strong positive association. For unemployed individuals, the experimental reservation wage increases on average by around one Euro for every Euro increase in the survey measure. For employed individuals, the association between the two measures is weaker, but still positive and statistically significant. We show that these results are robust to selection into the experiment, and that demographic variables have a similar influence on both reservation wage measures.
Keywords: C83; C91; J22; 330; reservation wage; labor supply; search; validation of survey measures